Normal left atrial diameter is associated with better performance on a cognitive screener among a cohort of ischemic stroke patients - Gootee, Emma; Stein, Colin; Walker, Alex; Daneshvari, Nicholas O.; Blaha, Michael J.; Lima, Joao A. C.; Gottesman, Rebecca F.; Johansen, Michelle C. (Frontiers in Neurology, 2022)
Background Cardiac structure is an important determinant of ischemic stroke (IS) etiology; however, whether an association between cardiac structural markers and cognition post-IS exists is not yet established. The aim of this study is to examine the association between LAD and LVEF with cognitive performance among IS patients. Methods IS patients admitted to the Johns Hopkins Hospital (2017–2019) underwent transthoracic echocardiography. IS was classified (TOAST) by a masked reviewer. Left atrial diameter (LAD) was evaluated as a non-linear continuous variable with one spline knot at 4 cm; left ventricle ejection fraction (LVEF) was dichotomized, then further evaluated as a non-linear continuous variable with spline knots at 50% and 70%. Patients were contacted by telephone on average 422 days post-stroke and administered the Six-Item Screener (SIS) to assess for dementia. SIS scores were dichotomized into low and high, imputing low scores for non-answerers. Multivariable logistic regression determined the association of SIS category with LAD or LVEF. A sensitivity analysis re-evaluated the association between SIS category and LAD, excluding participants with atrial fibrillation (AF). Results Participants (N = 108) were on average 61 years old (range = 18–89 years), 55% male, and 63% Black. Among patients considered to have a normal LAD (≤ 4 cm), a 1 mm larger LAD was associated with 1.20 greater odds (95%CI = 1.05–1.38) of scoring in the high SIS category in the final adjustment model. This association remained significant when excluding participants with prevalent AF. There was no association between a 1 mm larger LAD and SIS category among patients with a LAD >4 cm in both the primary analysis and the sensitivity analysis. There was no association between LVEF and SIS category. Conclusions In this prospective study, among ischemic stroke patients with a LAD within the normal range, a 1 mm increase in LAD was associated with higher scores on a telephone cognitive battery, without an association found among those with a LAD >4 cm.